The ROLE OF HERBAL ANTIFUNGAL AGENTS FOR THE MANAGEMENT OF FUNGAL DISEASES: A SYSTEMATIC REVIEW - KUSUM KAUSHIK; SHWETA AGARWAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Nowadays, fungal infection of skin is one of the most common dermatological problems worldwide. It has been investigated that 40 million people suffer from fungal infections. Superficial and subcutaneous fungal infections affect the skin, keratinous tissues, and mucous membranes. The dermatophytic infections, superficial candidiasis of the mouth, skin, or genital tract and infections due to Malassezia, such as pityriasis versicolor and Malassezia folliculitis are the main afflicting conditions. Systemic fungal infections may be caused by either an opportunistic organism that infects an at-risk host or may be associated with a more invasive organism or may be endemic to a specific geographical area. The most frequently encountered pathogens are Candida albicans and Aspergillus spp. but other fungi such as non-albicans Candida spp. are increasingly important in causing systemic fungal infections. There are numerous antifungal agents used clinically to treat fungal infections, i.e., azoles, allylamines, echinocandins, griseofulvin, and flucytosine. The course to modern treatment has not been without its problems and complications, particularly the drug resistances. Phytochemistry of various plant species has indicated that the phytochemicals could be a better source of medicine as compared to synthetically produced drugs. Natural medicines from a plant origin are still used as therapeutic agents, especially for treating bacterial, fungal, viral, protozoal, helminthic infections, etc. This review focuses on the use of plant constituents to prevent fungal infections caused by various pathogens. Hence, it will be proved beneficial for the drug industries.